Methods of Da’wah in Strengthening Religious Moderation in Indonesian Islamic Schools - Iskandar Iskandar; Abd. Wahidin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article aims to identify da’wah strategies in fostering religious moderation among students at MAN 2 Parepare through the strengthening of cooperation, assimilation, and acculturation skills. The approach used is action research, with data collection methods including Focus Group Discussions (FGDs), interviews, and observation. Data analysis was conducted using the Urgency, Seriousness, Growth (USG) approach. The research findings indicate that the Bil Hikmah (preaching with wisdom) and Tadarruj (gradual) methods received the highest scores at 4.88 points, highlighting an urgent need to strengthen these methods among teachers. In terms of student development, outbound activities proved to be an effective strategy. The ‘Blindfolded Maze’ outbound activity is prioritised to build students’ cooperation skills, whilst the ‘Cross-Cultural Cooking Day’ serves as the primary means to strengthen students’ assimilation. Furthermore, the ‘Cultural Exchange Simulation’ is recommended to enhance students’ acculturation skills, which contributes to the formation of a moderate religious character. These findings contribute to providing practical guidance for enhancing religious moderation through innovative da’wah approaches and outbound activities relevant to students’ needs. The implications of this research are the need to adopt and strengthen da’wah strategies based on real-world needs to foster a generation that is religiously moderate and capable of living amidst cultural diversity.